1997
DOI: 10.1136/gut.40.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Healing with basic fibroblast growth factor is associated with reduced indomethacin induced relapse in a human model of gastric ulceration.

Abstract: Background-Acid stable basic fibroblast growth factor (bFGF) promotes angiogenesis and healing of gastric ulcers in rats and reduces subsequent non-steroidal anti-inflammatory drug (NSAID) induced relapse. Aims-To test in a double blind, placebo controlled, three way crossover study whether bFGF promotes healing and reduces subsequent relapse in a human model of gastric ulceration. Subjects-Twelve healthy volunteers. Methods-Subjects took aspirin 900 mg twice daily (days 1-3) with bFGF 01 mg twice daily or cim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In humans, the acid-stable mutein of bFGF, CS23, has been shown to accelerate ulcer healing in patients with treatment-refractory ulcerations due to non-steroidal anti-inflammatory drugs (Hull et al, 1995) and to reduce indomethacin induced gastric ulcer relapse (Hull et al, 1997).…”
Section: Basic Fibroblast Growth Factormentioning
confidence: 99%
“…In humans, the acid-stable mutein of bFGF, CS23, has been shown to accelerate ulcer healing in patients with treatment-refractory ulcerations due to non-steroidal anti-inflammatory drugs (Hull et al, 1995) and to reduce indomethacin induced gastric ulcer relapse (Hull et al, 1997).…”
Section: Basic Fibroblast Growth Factormentioning
confidence: 99%
“…The availability of mice with interrupted genes for decorin and biglycan, respectively, opens up new ways for studying the role of the two proteoglycans during gastric ulcer healing in greater detail. However, from the data presented in this study it appears unlikely that the two proteoglycans participate in mediating the bene cial effect of an acid-stable FGF-2 analogue on ulcer healing previously described by us (22) as well as others (21).…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, we have studied the in uence of intragastral application of an acidstable mutein of FGF-2 (CS23). FGF-2 has been shown to accelerate ulcer healing in animal models (20) as well as in man (21). In a previous study utilizing FGF-2, we demonstrated an increased matrix deposition upon CS23 application, whereas no differences in procollagen I mRNA (22) and the expression of matrix metalloproteinase-2 mRNA were found.…”
mentioning
confidence: 88%
“…Although other studies [9] performed high quality procedures in a similar way, the number of endoscopies and/ or biopsies taken is subject to intensive discussion (table 5). We have just completed a study in HV, in which 10 individuals underwent a total of 8 endoscopies with a cumulative number of 240 biopsies.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…Table 5. Study details of [9] 12 healthy volunteers Double-blind, three-way, placebo-controlled study 15 endoscopies and less than 48 biopsies/volunteer 1/12 could not tolerate endoscopy beyond first treatment period 9 episodes of adverse events, no serious adverse events Table 6. Key issues for ethical research involving HV Definition of limits (maximum number of biopsies, cross-over treatments, number of endoscopies, time for one endoscopy procedure) Limits for salary (to guarantee sufficient motivation for participation) Testing of clinically relevant outcomes (improved drug safety, drug interactions) Minimum follow-up observation period after study completion Application of same safety standards as in patient studies Obligatory report of discomfort/intolerance for future trials tified if the expected improvement in scientific knowledge is likely to contribute to routine clinical practice (e.g.…”
Section: Considerations To Be Implemented In Future Recommendationsmentioning
confidence: 99%